ASPEK HUKUM - Pandi Ahmad Jawara; Khairun Nisa Br Tarigan; Rendy Prayuda (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
This article discusses the analysis of business feasibility studies from a legal perspective, especially regarding the legality of business entities. The main objective is to examine the legality aspect in depth. Legality is a crucial element in a business because it is closely related to third parties and functions to protect companies that operate honestly and in good faith (te goeder trouw). Legality plays an important role in supporting the growth of the business sector in a region or country, because official recognition of a business entity by the community can only be obtained through legality. In order to be legally valid, the legality of a company must be in accordance with applicable laws and regulations. Thus, the company will receive legal protection through official documents that are recognized. The government also needs to ensure that the process of issuing business permits is carried out based on clear legal provisions to encourage business development in a region. The benefits of company legality include legal protection, promotional media, proof of compliance with regulations, and efforts to prevent losses due to unwanted things.